تحضير فحم منشط إنطلاقا من سعف النخيل وتطبيقه في إزالة صبغة أزرق الميثيلين من محلول مائي - شيماء, عامر; مروة, بدر الدين; سعاد, عثماني (University of El-Oued, 2020)
"تضمنت الدراسة الحالية تحضير وتشخيص فحم منشط من سعف النخيل، اشارت تقنيات التشخيص المختلفة مثل التحليل الطيفي بالاشعة تحت الحمراء (FT-IR) والمجهر الالكتروني الماسح (SEM)، إلى أن الفحم المنشط المحضر يحتوي على العديد من المجموعات الوظيفية السطحية، ووجود مسامات على السطح. بالإضافة إلى دراسة قدرة امتزاز الفحم المحضر على صبغة أزرق الميثيلين من محلول مائي، كانت المساحة السطحية النوعية (202 m2/g)، مما يمنح القدرة العالية والجيدة للفحم المنشط على الامتزاز، وكانت نتائج إيزوتارم الامتزاز مطابقة لنموذج لانجمير مع كمية إمتزاز عظمى (113.76 mg/g). " "Present work included the preparation and diagnosis of activated charcoal from palm leaves. Various diagnostic techniques such as infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM) have indicated that the prepared activated carbon contains many surface functional groups and the presence of pores on the surface. In addition to study of adsorption ability of the prepared carbon to methylene blue dye from aqueous solution, the specific surface area was (202 m2/g), which gives the high and good adsorption ability of the activated carbon on adsorption, results of the adsorption isotherm were identical to the Langmuir model with maximum amount of adsorption (113.76 mg/g). "
Génie chimiqueمذكرة ماستر تخصص
Keywords: السعف، تلوث المياه، فحم منشط، امتزاز، أزرق الميثيلين.; fronds, water pollution, activated carbon, adsorption, methylene blue.